Окислительная очистка жидких радиоактивных отходов от органических соединений и радионуклидов перманганатом калия - Руденко, Л.И.; Джужа, О.В.; Хан, В.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The oxidizing purification of liquid radioactive waste (LRW) from organic substances and radionuclides with the use of a water solution of potassium permanganat is investigated. At a mass ratio of organic substances and a 5% solution of potassium permanganat of 1.5 : 1 in a strongly sour environment, the dichromate oxidizability decreases from 2360 to 100 mg O2/dm3, the concentration of uranium from 42 to 1.3 mg/dm3 and the activity of 90Sr from 2.2 • 107 to 3.5 • 104 Bq/dm3 decrease. The basic opportunity of the oxidizing purification of LRW with the use of a water solution of potassium permanganat for the preliminary preparation of LRW at a stage prior to the evaporating devices of the Chernobyl NPP is shown.